Digital and Green Synergies: How Malaysia is Cutting Carbon Emissions through Supply Chain Innovation, Renewable Energy and Upcycling? - Sibghatullah, Amena; Sohail, Mariam; Abdullah, Firdaus; Ma’in, Masturah; Rakhimova, Mohinur (International Journal of Energy Economics and Policy, 2025)
This paper aims to analyze the influence of the digital economy, green supply chain management, renewable energy consumption, and upcycling on carbon emissions in Malaysia. These are crucial objectives as the country strives to achieve economic development without compromising the environment, given that the two are in an unending conflict in society. Thus, the study’s objective is to examine the role of digitalization, renewable energy use, green supply chain management and upcycling in carbon emissions in Malaysia. It aims to establish whether these factors are statistically significant and offer policy implications for projecting their efficiency gains. Therefore, a quantitative method, using the employed pooled ordinary least squares (POLS) regression analysis, was used to test the correlation between key variables of sustainability and carbon emissions for the period of 2014-2024. The Durbin-Watson test and the VIF analysis were also carried out to test the model that was used to diagnose the independent variables. The outcome reveals that increasing the digital economy’s scale and renewable energy consumption reduces carbon emissions. As for the green supply chain management and upcycling practices, there is no significant correlation between them, which can be attributed to the fact that the implementation of such practices has not reached maturity. Some barriers include lack of infrastructure, policies and inadequate funding that may seasonally limit their maximum capacity. The study implies that digitalization and renewable energy, which mitigate carbon emission practices, work well. In contrast, green supply chain management and upcycling need more policy encouragement and well-developed infrastructure. For Malaysia to achieve its long-term reduction targets, it is necessary to have better policies that cover sustainability laws in industries, provide incentives for green technology and invest in upcycling industries.